The Impact of Family Socio-Economic Conditions on the Learning Motivation of Students of SMP Negeri 6 Huamual in Lokki Village, Huamual District, West Seram Regency - Pinoa, Wiclif Sepnath; Tentua, Matrix Vecky; Manakane, Susan Evelin (Jurnal Pendidikan Geografi Unpatti, 2023)
This research investigates the relationship between family socio-economic conditions and students' extrinsic learning motivation in Lokki Village, Huamual District, West Seram Regency. The research method used is qualitative, with a descriptive approach involving data collection through interviews, observations, and surveys. The research findings reveal that family socio-economic conditions significantly impact students' extrinsic learning motivation. Parents with low levels of education need to be more capable of providing practical encouragement and guidance in their children's education. Limited livelihoods and family income also restrict students' access to the necessary educational resources and facilities. Health issues and the lack of facilities such as internet access and study rooms also affect students' learning motivation. Interventions that consider family socio-economic conditions are needed to enhance learning motivation.